2002
DOI: 10.1007/s10350-004-6302-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Dynamic Graciloplasty for Fecal Incontinence

Abstract: Dynamic graciloplasty was successful in the majority of patients with end-stage fecal incontinence. This result was usually achieved by 12 months after surgery in patients who did not have stomas and by 18 months in patients who had stomas at the time of dynamic graciloplasty surgery. These various improvements conferred by dynamic graciloplasty persisted during the two-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 24 publications
6
79
1
9
Order By: Relevance
“…Wexner and colleagues 31 reported that at 2 years postoperation, out of 115 patients from a multicentre study, 15% were completely continent and 42% had 50-99% continence; it is not clear whether 'continence' implied continence to solid and liquid stool. This compares with the RLH ESGNS study where, at 2 years, 17% were never incontinent to solid or liquid stool and 47% were incontinent less than once per week.…”
Section: Comparison Of Our Results With Previously Published Seriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wexner and colleagues 31 reported that at 2 years postoperation, out of 115 patients from a multicentre study, 15% were completely continent and 42% had 50-99% continence; it is not clear whether 'continence' implied continence to solid and liquid stool. This compares with the RLH ESGNS study where, at 2 years, 17% were never incontinent to solid or liquid stool and 47% were incontinent less than once per week.…”
Section: Comparison Of Our Results With Previously Published Seriesmentioning
confidence: 99%
“…Recent multicentre [29][30][31] studies have confirmed that, for between 50 and 70% of patients, ESGNS can improve or restore continence. A high incidence of major morbidity, including ongoing bowel evacuatory disorders, has been reported.…”
Section: The Evidence Basementioning
confidence: 99%
See 1 more Smart Citation
“…La NRS surge como resultado del desarrollo de la neurofisiología defecatoria, como una opción terapéutica para los casos con IF sin defecto anatómico objetivable, en los que históricamente ha existido un vacío terapéutico (6,10,17). La NRS, mediante la estimulación eléctrica de las fibras sensoriales aferentes sacras, consigue una mejora en el equilibrio de interacción entre las distintas estructuras implicadas en el mecanismo defecatorio, actuando sobre centros reflejos neurológicos (no sólo medulares, sino también pontinos), con repercusiones a nivel de la contractilidad, distensibilidad y sensibilidad rectal (24,25). Así, a través de la estimulación de fibras aferentes sacras, se produce una neuromodulación sobre los centros reflejos defecatorios, dando como resultado una mejora sobre la continencia anal (6,10,17).…”
Section: Discussionunclassified
“…Otra técnica es la graciloplastía dinámica, que es la creación de un esfínter con músculo gracilis que ha sido sometido a estimulación eléctrica continua, lográndose de esta manera resistencia a la fatiga. Estos métodos se emplean en pacientes con lesiones estructurales graves del esfínter y consiguen la mejoría de la incontinencia en aproximadamente el 60% de los pacientes a corto plazo y 62% a 2 años de seguimiento 34 .…”
Section: Neoesfínteresunclassified